Trunk muscularity in throwers - Tanaka, N. I.; Komuro, T.; Tsunoda, N.; Aoyama, T.; Okada, M.; Kanehisa, H. (International Journal of Sports Medicine, 2013)
This study aimed to examine and compare the trunk muscularity of track and field throwers and non-athletes, and its predictive value to the physical performance of the athletes. Using a magnetic resonance imaging method, the skeletal muscle volume (SMV) of the trunk (SMVtrunk) was determined in 19 strength trained athletes and 18 non-athletes. Also, the SMV of upper, middle and lower regions of the trunk was calculated in every 33% of the trunk length. For the athletes, the maximum weight (1RM) of squat, high clean, and deadlift, and shot forward throwing score were measured. The SMVtrunk in the athletes was 10% greater than that of non-athletes, with a larger difference in the upper region of the trunk. Step-wise multiple regression analysis indicated that the SMV of the lower region was a significant contributor for predicting the 1RM values of the 3 tasks, as well as the shot forward throwing score. The current results indicate that, while the muscularity of the trunk in track and field throwers is characterized by predominant development in the upper region, the muscularity in the lower region is a determinant factor for the 1RM values of the squat, high clean, and deadlift and shot forward throwing score.